2013
DOI: 10.1378/chest.12-2405
|View full text |Cite
|
Sign up to set email alerts
|

Altered Circadian Rhythmicity in Patients in the ICU

Abstract: The findings indicate that circadian rhythms are present but altered in patients in the ICU, with the degree of circadian abnormality correlating with severity of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 56 publications
(79 reference statements)
3
81
0
5
Order By: Relevance
“…Recent data support the use of core body temperature or 6-sulfatoxymelatonin as phase markers in critically ill patients. Fever, organ dysfunction, and medications may, however, render these measurements unreliable (13,25).…”
Section: Circadian Rhythm Alterations In Critically Ill Patientsmentioning
confidence: 99%
“…Recent data support the use of core body temperature or 6-sulfatoxymelatonin as phase markers in critically ill patients. Fever, organ dysfunction, and medications may, however, render these measurements unreliable (13,25).…”
Section: Circadian Rhythm Alterations In Critically Ill Patientsmentioning
confidence: 99%
“…45 In a recent study, Gazendam and colleagues 46 found that acrophases were shifted (advanced or delayed) in 81% of patients, but that this shift was stable across days in each individual. In contrast, in a large cohort of 137 patients investigated after thoracic or vascular surgery, core body temperature showed no circadian rhythmicity in most patients during the first 3 postoperative days.…”
Section: Circadian Rhythms and Melatonin In Intensive Care Unit Patientsmentioning
confidence: 99%
“…38,39 Therefore, although suppression of biological rhythms is an energy-preserving mechanism that is beneficial under stress, 40 the effects of long-term disruption of rhythms are pathologic, 41 leading to worse outcomes and delayed recovery. 42 Recent evidence supported the potential of using circadian systems as a therapeutic target. 43 …”
Section: Ra and Circadian Rhythmsmentioning
confidence: 99%